Movie-Struck Girls : Women and Motion Picture Culture after the Nickelodeon - Stamp, Shelley, 1963- (Book collections on Project MUSE., 2000)
Movie-Struck Girls examines women's films and filmgoing in the 1910s, a period when female patronage was energetically courted by the industry for the first time. By looking closely at how women were invited to participate in movie culture, the films they were offered, and the visual pleasures they enjoyed, Shelley Stamp demonstrates that women significantly complicated cinemagoing throughout this formative, transitional era. Growing female patronage and increased emphasis on women's subject matter did not necessarily bolster cinema's cultural legitimacy, as many in the industry had hoped, for women were not always enticed to the cinema by dignified, uplifting material, and once there, they were not always seamlessly integrated in the social space of theaters, nor the new optical pleasures of film viewing. In fact, Stamp argues that much about women's films and filmgoing in the postnickelodeon years challenged, rather than served, the industry's drive for greater respectability. White slave films, action-adventure serial dramas, and women's suffrage photoplays all drew female audiences to the cinema with stories aimed directly at women's interests and with advertising campaigns that specifically targeted female moviegoers. Yet these examples suggest that women's patronage was built with stories focused on sexuality, sensational thrill-seeking, and feminist agitation, topics not normally associated with ladylike gentility. And in each case concerns were raised about women's conduct at cinemas and the viewing habits they enjoyed, demonstrating that women's integration into motion picture culture was not as smooth as many have thought.